Socio-Psychological Analysis of the Typology of Consumers of Higher Education Institutions’ Educational Services - H. CHERUSHEVA (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2024)
The dynamic development of educational services in the context of the new socio-economic reality is an important and influential factor in enriching the intellectual resources of both individuals and society as a whole. The provision of educational services as a key area of activity in the labor market reflects socio-economic transformations and serves as a determining factor of the competitiveness of any country’s economy.The laws of the market economy constitute the fundamental economic basis for the development of the educational services market in Ukraine. At the same time, educational organizations, while possessing a European-type structure, retain their individual and regional characteristics, taking into account their level, professional orientation, as well as academic freedom aimed at meeting the needs of target consumers of educational services.The article reveals conceptual approaches to defining the notions of “educational services” and “consumers of educational services.” Based on theoretical analysis and empirical research, the main educational organizations forming the education system as a social institution for providing educational services, as well as the forms of formal and non-formal education in Ukraine, are identified.Special attention is paid to the analysis of the main categories of consumers of educational services and to the socio-psychological analysis of factors influencing the educational intentions of young people both during their professional training in higher education institutions and in the period of their professional development. Based on the research findings, a typology of different groups of the consumer audience has been developed, each characterized by its own motives and decision-making factors.